The Role of Microaspiration in the Pathogenesis of Gastroesophageal Reflux-related Chronic Cough - Özdemir, Pelin (J Neurogastroenterol Motil, 2017)
BACKGROUND/AIMS: Gastroesophageal reflux disease (GERD) is one of the main causes of chronic cough. We evaluated the role of microaspiration in the pathogenesis of reflux-related cough by determining the amount of lipid-laden macrophages (LLMs) in bronchoalveolar lavage (BAL) specimens. METHODS: A total of 161 cases of chronic cough were evaluated, and 36 patients (average age 48.2 years) were recruited for this single center prospective study. Patients with a history of smoking, angiotensin converting enzyme inhibitor usage, any abnormality on pulmonary function tests, abnormal chest X-rays, occupational or environmental exposures, or upper airway cough syndrome were excluded. GERD was evaluated by 24-hour esophageal impedance-pH monitoring. BAL specimens for LLM determination were obtained from 34 patients by flexible bronchoscopy. RESULTS: Patients with pathological intra-esophageal reflux according to multichannel intraluminal impedance and pH monitoring had higher LLM positivity in BAL specimens than patients without pathological reflux (8/14 in reflux positive group vs 1/22 in reflux negative group; P = 0.004). The BAL cell distribution was not different between the 2 groups (P = 0.574 for macrophages, P = 0.348 for lymphocytes, P = 0.873 for neutrophils and P = 0.450 for eosinophils). CONCLUSIONS: Our results confirm the role of the microaspiration of refluxate in the pathogenetic mechanism of chronic cough. While bronchoscopy is indicated in patients with chronic cough, in addition to the routine airway evaluation, BAL and LLM detection should be performed. LLM can be used to diagnose aspiration in reflux-related chronic cough. Future studies are needed to evaluate the response to anti-reflux medications or surgery in patients with LLM positivity.